CHALLENGES IN PUBLIC HEALTH SYSTEMS: ADDRESSING INEQUITIES IN RURAL AND REMOTE AREAS: JPUMHS;2024:14:04,1-3. http://doi.org/10.46536/jpumhs/2024/14.0 4.554 - Jamali, Anwar Ali (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
As long as urban & underserved zones through rational right of entry to healthcare facilities is solitary of the chief problems fronting worldwide community well-being schemes. Significant strategies for undertaking these matters comprise talking healthcare discriminations, leveraging tools identical telemedicine, & emerging robust vaccination plans. To decrease the healthcare breach & assurance that entirely populaces, irrespective of place, have admittance to eminence care in an appropriate way, these problems necessity be logically spoken.